PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KEUANGAN PADA LEMBAGA PEMASYARAKATAN KELAS IIB KABUPATEN BIREUEN - Rahmat, Mustiwal; Iba, Zainuddin; Syaripuddin, Syaripuddin (LPPM-UNIKI, 2023)
This research was conducted on Class IIB Bireuen Penitentiary employees who analyzed financial performance based on a study of the factors of transformational leadership style, organizational culture and job satisfaction. With descriptive and verification analysis methods using multiple linear regression models. The results showed that the correlation of transformational leadership style variables, organizational culture and job satisfaction was very strong on the financial performance variable so that the contribution was 89,9%. However, partially there is no significant influence of transformational leadership style or organizational culture on financial performance. Significant influence only occurs in the variable job satisfaction.